2002
DOI: 10.1007/bf02987591
|View full text |Cite
|
Sign up to set email alerts
|

The role of the egg jelly coat in protectingHyla regilla andBufo canorus embryos from ultraviolet B radiation during development

Abstract: Based on the results in this study it seems unlikely that the egg jelly coat is playing a crucial role in protecting developing embryos from the impact of UVB radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, other studies have found that melanin does not protect exposed animals from the damaging effects of UVBR (e.g., Belden and Blaustein 2002c). Hansen et al (2002) have shown that the egg mass jelly of Hyla regilla embryos displayed no absorption in the UVR range. Removal of the jelly coat of both H. regilla and Bufo canorus (Yosemite toad) embryos and subsequent exposure to UVBR in a solar simulator also demonstrated that the jelly played no apparent role in protecting embryos; hatching success was similar in eggs with and without the egg jelly (see also Rasanen et al 2003).…”
Section: Effects Of Uvbr Exposure On the Rate Of Amphibian Developmenmentioning
confidence: 96%
“…However, other studies have found that melanin does not protect exposed animals from the damaging effects of UVBR (e.g., Belden and Blaustein 2002c). Hansen et al (2002) have shown that the egg mass jelly of Hyla regilla embryos displayed no absorption in the UVR range. Removal of the jelly coat of both H. regilla and Bufo canorus (Yosemite toad) embryos and subsequent exposure to UVBR in a solar simulator also demonstrated that the jelly played no apparent role in protecting embryos; hatching success was similar in eggs with and without the egg jelly (see also Rasanen et al 2003).…”
Section: Effects Of Uvbr Exposure On the Rate Of Amphibian Developmenmentioning
confidence: 96%
“…Perotti and Diéguez [92] also found that the optical properties of the egg jelly envelope surrounding the embryo is also correlated with embryonic melanin concentration: the egg jelly of the species with the lowest embryonic melanin concentration (P. thaul) had the highest UVR absorbance whereas the egg jelly of the species with the highest embryonic melanin concentration (R. spinulosa) had the lowest UVR absorbance. Several additional studies have similarly shown that the UVR absorbance by the egg jelly envelope varies with wavelength and among species [93][94][95][96][97], and also the protective role of the jelly envelope varies among populations within a species along an elevation gradient [98]. Such research indicates that for some species the jelly envelope may provide adequate protection against UVR for the embryo, whereas others may rely on alternative defence strategies such as pigmentation, behavioural avoidance (e.g.…”
Section: Uvr-screening Compounds and Egg Jellymentioning
confidence: 97%
“…The absorption maximum of the jelly was at 275 nm in various anuran species (Ovaska et al 1997). Hansen et al (2001) noticed that efficient protection against UV-B would require a maximum UV-B absorption between 294 and 305 nm, which represents the most deleterious range of UV-B wavelengths. In lower UV-B doses than those used in our experiments, the jelly did not play an apparent role in photoprotection in R. temporaria (Räsänen et al 2003), Hyla regilla, or Bufo canorus (Hansen et al 2001).…”
Section: Discussionmentioning
confidence: 99%